Направления оптимизации пространственного развития региона (Географический вестник=Geographical bulletin, 2017)
Рассматриваются актуальные вопросы пространственной организации региона, определяются проблемы, обусловленные несовершенством опорного каркаса территории. Предлагаются направления оптимизации территориального развития: выявление, корректирование и стимулирование ядер тяготения, или полюсов роста; социально-экономическая интеграция микрорайонов (округов) на основе выделенных полюсов роста с последующим созданием условий для развития центра и периферии.THE  OPTIMIZATION'S WAY OF SPATIAL DEVELOPMENT OF THE REGION There are actual questions that are being disclosed regarding the vast organization of the region. The problems are being revealed, caused by non perfective supported frame of the territories: lack of the optimal pole rise, lack of optimal system of settling, non proficiency of transportation picture, non perfective administrative-territory division and absence of the territory committee organizations; and disproportions within the region’s development.  There are certain propositions for optimization the territory development: exposing, correcting and stimulating the core gravitations or pole rises; the socio-economic integration of micro-regions (districts) on the basis of highlighted pole rises with the subsequent condition’s establishment in order to develop the centers and peripheries;  provision of the industrial, engineer, housing and communal services and social infrastructure objects, that assists the expansion of internal and international relations and increases the quality of living conditions.